2010
DOI: 10.3109/09637481003591574
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyoxyethylene sorbitan esters and sodium caseinate on physicochemical properties of palm-based functional lipid nanodispersions

Abstract: The main objective of the present study was to investigate the effect of polyoxyethylene sorbitan esters and sodium caseinate on physicochemical properties of palm-based functional lipid nanodispersions prepared by the emulsification-evaporation technique. The results indicated that the average droplet size increased significantly (P < 0.05) by increasing the chain length of fatty acids and also by increasing the hydrophile-lipophile balance value. Among the prepared nanodispersions, the nanoemulsion containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
3
1
Order By: Relevance
“…This finding might be explained by the increasing interference caused by the growing number of polysorbate molecules, which prevented the efficient diffusion of the organic phase into the aqueous phase. To the best of our knowledge, there are three other studies by Anarjan and Tan (2013), Cheong, Mirhosseini, and Tan (2010) and Saberi et al (2013), which were similar to our study in the sense that all three studies involved the fabrication of different nanoemulsions/nanodispersions by using Tween 20, 40, 60 and 80 (in the case of Cheong et al (2010), they used only Tween 20, 60 and 80). In their respective studies, Anarjan and Tan (2013) and Cheong et al (2010) found that, among all the Tween emulsifiers used, Tween 20…”
Section: Effects Of Different Polysorbate (Tween) Emulsifierssupporting
confidence: 80%
See 2 more Smart Citations
“…This finding might be explained by the increasing interference caused by the growing number of polysorbate molecules, which prevented the efficient diffusion of the organic phase into the aqueous phase. To the best of our knowledge, there are three other studies by Anarjan and Tan (2013), Cheong, Mirhosseini, and Tan (2010) and Saberi et al (2013), which were similar to our study in the sense that all three studies involved the fabrication of different nanoemulsions/nanodispersions by using Tween 20, 40, 60 and 80 (in the case of Cheong et al (2010), they used only Tween 20, 60 and 80). In their respective studies, Anarjan and Tan (2013) and Cheong et al (2010) found that, among all the Tween emulsifiers used, Tween 20…”
Section: Effects Of Different Polysorbate (Tween) Emulsifierssupporting
confidence: 80%
“…By contrast, Saberi et al (2013) noted that among these four types of Tween emulsifiers, Tween 80 produced nanoemulsions with the smallest particle sizes, whereas the largest particle size was obtained when Tween 60 was used, although both Tween 60 and Tween 80 have similar HLB values (the HLB for Tween 60 is 14.9 and the HLB for Tween 80 is 15.0). In comparing our findings with all three studies, we found that our observations were similar to those of Saberi et al (2013), but they were the exact opposite of the observations noted by Anarjan and Tan (2013) and Cheong et al (2010). In our case, Tween 80 produced smaller particle sizes when compared with Tween 20.…”
Section: Effects Of Different Polysorbate (Tween) Emulsifierscontrasting
confidence: 68%
See 1 more Smart Citation
“…Tan and Nakajima [ 6 ] successfully prepared β-carotene nanodispersions using different polyglycerol esters of fatty acids as emulsifier. Yuan et al [ 7 ] and Cheong et al [ 15 ] have reported the characterization of β-carotene oil-in-water nanoemulsions and palm-based functional lipid nanodispersions, respectively, prepared by high pressure homogenization using a series of polyoxythylene sorbitan esters of fatty acids as emulsifiers. Leong et al [ 16 ] have also studied the influence of different sucrose esters of fatty acids as emulsifiers on the physicochemical properties of phytosterol nanoemulsions.…”
Section: Introductionmentioning
confidence: 99%
“…The stability behavior of oil-in-water emulsions based on caseins is related to their structure and mechanical properties of adsorbed layers at the surface of the droplets [ 10 ]. When surfactants are used together with casein, competitive adsorption of two components toward the interface occurs [ 11 ], thereby leading to some emulsion instability by reduced steric and electrostatic repulsion [ 12 ]. However, very low concentrations of surfactants improve the role of casein at the oil-in-water interface at acidic pH [ 13 ], and the pH of milk (6.67) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%